URGENSI PENDIDIKAN PADA ANAK USIA DINI DI ERA DAN TRANFORMASINYA DALAM METODE PEMBELAJARAN KONTEMPORER - Zahratur Rahma; Muhammad Alfatih Suryadilaga (UIR PRESS, 2021)
Abstract: This article discusses the urgency of early childhood education. Early childhood education begins when the child is still in the womb using Islamic teaching methods. At an early age, children can have a responsive attitude to stimuli given directly by their parents which are sometimes not realized by the environment around the child. Some hadits that explain the stages of children's education informing children to become children, who are useful for the religion, the nation, society, and both parents The purpose of this study is to describe the Islamic opinion about education in early childhood, how to educate children, and methods of Islamic education. The learning methods are exemplary, practice, games, songs, and stories, targib wa tarhib. This method is part of the urgency of early childhood education.